It is Fear, Not Disgust, That Enhances Memory: Experimental Study on Students in Bandung - KaYan KaYan; Henndy Ginting; Cakrangadinata Cakrangadinata (ANIMA Indonesian Psychological Journal, 2016)
A number of research findings have found the impact of emotion on memory. Some researchers stated that disgust has more impact on memory, however according to the current study the effect of fear cannot be ignored. Both disgust and fear are examples of negative emotion that may have a significant influence on behavior, such as in the attempt of creating a healthy lifestyle. The current study involved an experiment where participants were asked to memorize and recall four randomly displayed picture categories that elicit emotions of disgust, fear, joy, and neutral emotion. They also filled out a DS-R (Disgust Scale-Revised) questionnaire and a supporting questionnaire about healthy lifestyle. Analysis of the results showed that disgust did not show an effect on memory, but fear instead did. This is related to the fact that most participants showed a low degree of disgust, and so it was not considered a significant emotion that affected memory compared to fear. In addition, physiologically fear and disgust are managed by different parts of the brain and thus it was assumed that they will have a different impact on memory. The findings implied that, in campaigning for a healthier lifestyle, fear emotion need to be instilled in people.